Building Information Modelling (BIM) based framework for construction and demolition waste estimation and management - Abdul Mueed Yousfani,; Muhammad Saleem Raza,; Muhammad Ali Moriyani,; Tauha Hussain Ali, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Modern day world gives huge importance to sustainable construction and demolition (C&D). Governments and companies all over the world, are striving to develop methods, which reduce waste. A good step is to reduce, reuse and recycle (3R principle) construction and demolition waste. Essential for these activities is to have proper estimates of waste, that would be generated on construction and demolition of structures. Current practice in construction industry compromises on accurate estimation and audit of waste produced and recycled in construction and demolition. Considering this anomaly, this research is conducted to develop a BIM based system, for better waste estimation. The system is aimed towards estimating total waste produced, along with classifying waste that could be recycled or that must be disposed after building demolition. Initially, available waste estimation systems and their limitations are analysed. Consequently, a waste estimation is performed on a residential building model designed in Revit structures software. Successively, the data from Revit is input to a software programmed in C++ language to get estimates of waste. The research results into formation of a framework that estimates waste for any building required to be demolished. The framework has capability of estimating amount of total waste generated along with the amount of recyclable and disposable waste. Along with that, the framework gives an estimate of the cost of total amount of waste produced, specifying amount saved on recycling/reusing.